2020
DOI: 10.1186/s12859-020-03931-6
|View full text |Cite
|
Sign up to set email alerts
|

An automated protocol for modelling peptide substrates to proteases

Abstract: Background Proteases are key drivers in many biological processes, in part due to their specificity towards their substrates. However, depending on the family and molecular function, they can also display substrate promiscuity which can also be essential. Databases compiling specificity matrices derived from experimental assays have provided valuable insights into protease substrate recognition. Despite this, there are still gaps in our knowledge of the structural determinants. Here, we compile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 67 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…To test mPARCE we selected a well-characterized protease system (PDB id 3tjv) bound to a 9-mer peptide substrate. The peptide covers the cleavage binding site from position S4′ to S4, including the catalytic region between S1′ and S1 [ 51 ]. The peptide consists of 9 natural amino acids, and the goal was to allow changes in four positions, covering both the flanking and core amino acids close to the catalytic site.…”
Section: Resultsmentioning
confidence: 99%
“…To test mPARCE we selected a well-characterized protease system (PDB id 3tjv) bound to a 9-mer peptide substrate. The peptide covers the cleavage binding site from position S4′ to S4, including the catalytic region between S1′ and S1 [ 51 ]. The peptide consists of 9 natural amino acids, and the goal was to allow changes in four positions, covering both the flanking and core amino acids close to the catalytic site.…”
Section: Resultsmentioning
confidence: 99%
“…On average the protease-binding peptides tend to be negatively charged, are smaller than the MHC peptide binders, and less hydrophobic. However, based on a study of proteases specificity profiles [ 27 ], the sequences can be diverse in terms of their physico-chemical properties such as the hydrophobicity and net charge. Therefore, challenges remain in the prediction of substrate cleavage patterns by machine learning and sequence-based methodologies, which can be aided by tools like PepFun.…”
Section: Resultsmentioning
confidence: 99%
“…In ref. [27], we found that several structural descriptors, which are normally not used for cleavage predictions (because of the lack of protease structures bound to complete substrates), can provide relevant insights about the enzyme specificity. The second type of interactions calculated with PepFun are the potential hydrogen bonds.…”
Section: Python Pepfun Py − M S T R U C T U R E − P [ Structure_file ] − C [Chain] − T [Threshold]mentioning
confidence: 99%
“…To accelerate the process of designing specific substrates, methods to generate and screen libraries of peptide sequences have been developed, including positional scanning libraries [27][28][29] , peptide microarrays 30,31 , fluorogenic peptides 32,33 , and other mixture-based peptide libraries 34,35 . These libraries are either degenerate or diversified at certain positions based on consensus cleavage motifs from the literature 36 or computational approaches to predict peptide sequences based on the structure of the active site of a target protease 37,38 (Fig. 1, step 2).…”
Section: Introductionmentioning
confidence: 99%